2019
DOI: 10.3168/jds.2018-15572
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and phenotypic analyses of exopolysaccharide biosynthesis in Streptococcus thermophilus S-3

Abstract: Streptococcus thermophilus, one of the most important industrial lactic acid bacteria, is widely used as a starter culture in the dairy industry. Streptococcus thermophilus S-3 isolated from Chinese traditional dairy products has shown great potential for the production of larger amounts of exopolysaccharides (EPS), which significantly affect the organoleptic properties of fermented milk products. To understand the relationship between the genotype and phenotype of S. thermophilus S-3 in terms of EPS biosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 42 publications
3
44
0
Order By: Relevance
“…be useful for extrapolating findings from one strain to another. In all cases understanding of the EPS biosynthesis in S. thermophilus may allow a better selection of strains or even their engineering for improved dairy and probiotic products (Xiong et al, 2019a).…”
Section: Biosynthesis Of Epsmentioning
confidence: 99%
“…be useful for extrapolating findings from one strain to another. In all cases understanding of the EPS biosynthesis in S. thermophilus may allow a better selection of strains or even their engineering for improved dairy and probiotic products (Xiong et al, 2019a).…”
Section: Biosynthesis Of Epsmentioning
confidence: 99%
“…Structurally, the EPS produced by S. thermophilus are heteropolysaccharides made up of oligosaccharide repeating unit synthetized in the cytoplasm by the action of a number of glycosyltransferases and branched chains containing glucose and galactose, rhamnose and sometimes N-acetyl-glucosamine and fucose (Doco et al, 1990;Petit et al, 1991;Dan et al, 2009). Genome-scale studies revealed that the EPS biosynthetic pathway in S. thermophilus involves the sugar uptake system, nucleotide sugar synthesis, polysaccharide synthesis, and export of EPS, which are controlled by several housekeeping genes and a cluster of EPS-related genes (Laws et al, 2001;Wu et al, 2014;Cui et al, 2017;Alexandraki et al, 2019;Xiong et al, 2019). In lactic acid bacteria (LAB), the typical EPS gene cluster was described to contain five highly conserved genes epsA, epsB, epsC, epsD, and epsE, and a variable region, which includes the genes for polymerases, flippases, and a variable number of glycosyltransferases and other modifying enzymes [reviewed in Zeidan et al (2017)].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, a number of S. thermophilus genomes have been published, and the whole genome information has improved the understanding of metabolic activities of this bacterium at the molecular level, including the biosynthesis of EPS and folate (Iyer et al, 2010;Cui et al, 2017;Li et al, 2018;Xiong et al, 2019), resistance to bacteriophage (Hao et al, 2018), proteolytic system (Tian et al, 2018), and carbohydrate metabolism (Prajapati et al, 2013), etc. Furthermore, the comparative genomic analysis of different S. thermophilus strains with various technological properties has advanced the development of knowledge about the relationship between genetic characters and phenotypic traits (Rasmussen et al, 2008;Vendramin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%